Beyond Administrative Compliance: Legal Advocacy for Substantive Transparency and Accountability in Regional Head Election Campaign Financing - Marvi De Queljoe; M. J. Saptenno; Adonia. I. Laturette; Elsa. R. M. Toule; Theo Samudri D. Rihi (Universitas Negeri Semarang, 2026)
Transparency and accountability of campaign finance are fundamental to safeguarding democratic integrity in Regional Head Elections. Although Indonesia's campaign finance regulations require disclosure and reporting, their implementation largely emphasizes procedural compliance rather than ensuring substantive transparency and accountability. This regulatory–implementation gap is reflected in formalistic reporting practices, potential underreporting, limited quality and accessibility of financial information, and weak oversight and enforcement mechanisms. This study examines the role of legal advocacy in strengthening substantive transparency and accountability of campaign finance by analyzing the existing regulatory framework and its implementation challenges. The research employs a normative legal method using statutory, conceptual, and case approaches to examine the coherence between campaign finance regulations, legal principles, and their implementation in electoral governance. The findings reveal that transparency and accountability constitute substantive legal principles that extend beyond compliance with reporting obligations. Although Indonesia's legal framework provides an adequate normative basis for campaign finance regulation, its effectiveness is undermined by pseudo-transparency, incomplete financial disclosure, restricted public access to campaign finance information, and ineffective audit and sanction mechanisms. The study argues that legal advocacy plays a strategic role in bridging the gap between legal norms and electoral practice by strengthening public oversight, improving information disclosure systems, enhancing the effectiveness of campaign finance audits, and reinforcing sanction enforcement. These findings contribute to the discourse on electoral law by demonstrating that legal advocacy is essential for transforming campaign finance transparency from a procedural obligation into a substantive mechanism that promotes democratic accountability and electoral integrity.